A STUDY ON CHARACTERISTICS STRENGTH OF HYBRID FIBRE REINFORCED SELF COMPACTING CONCRETE INCORPORATING - Suja, B.; Jenies, T.; Jaganathan, Mr.v. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Now a day’s usage of cement is increasing day by day which has to be reduced since production of cement emits approximately equal quantity of co2. For environmental purpose it is our responsibility to find a supplement for cement. Rice husk ash has been employed as an additive in many materials, including refractory brick, light weight concrete. It’s highly porous, light weight and has a high specific area. It contains 90% of amorphous silica and 5% alumina which make its highly pozzolanic. Use of rice husk ash improves the durability of concrete, economical and eco-friendly. Self-compacting concrete (SCC) is a flowing concrete mixture that is able to consolidate under its own weight. The highly fluid nature of SCC makes it suitable for placing in difficult conditions and in sections with congested reinforcement. And also addition of fibers in concrete which increases the duration of generating initial crack and reduces the initial shrinkage. Thus the project deals with addition of steel fiber as 0.75% and polypropylene as 0.25% incorporating rice husk ash as a partial replacement for cement in varying percentages up to 30% with increment of 5%. The main objective is to study the characteristics strength of hybrid fiber reinforced self-compacting concrete incorporating rice husk ash